Association of anger-related traits with SNPs in the TPH gene - Rujescu, D; Giegling, I; Bondy, B; Gietl, A; Zill, P; Möller, H-J (Molecular psychiatry, 2002)
Since both aggression-related traits and serotonergic activity are partially heritable and correlate inversely, variations in genes of the serotonergic system might then, to some extent, account for variations in aggression-related behavior. Tryptophan hydroxylase (TPH) is the rate limiting biosynthetic enzyme in the serotonin pathway and regulates levels of serotonin. Recently, a genetic variation in TPH has been associated with aggression and anger-related traits in volunteers. We investigated a sample of community-based healthy volunteers (n = 154) and suicide attempters (n = 86), a clinical population with a high risk for elevated impulsive aggression and related traits. The subjects were genotyped for a A218C and a A779C single nucleotide polymorphism (SNP) located in the TPH gene. All subjects were administered standard psychiatric interviews as well as self-report questionnaires for aggression, irritability and anger-related traits. For anger-related traits, a multivariate effect of the tryptophan hydroxylase genotype and an interaction effect for genotype and diagnosis was observed in healthy volunteers and suicide attempters after controlling for age and educational level. U-carriers in both groups showed higher scores for State Anger, Trait Anger and Angry Temperament. These findings support the hypothesis that the A218C and the A779C SNP in the TPH gene may be associated with anger-related traits in German samples.